Complete mitochondrial genome sequence of Nectogale elegans. (August 2014) - Huang, Ting; Yan, Chaochao; Tan, Zheng; Tu, Feiyun; Yue, Bisong; Zhang, Xiuyue
Abstract The elegant water shrew (Nectogale elegans) belongs to the family Soricidae, and distributes in northern South Asia, central and southern China and northern Southeast Asia. In this study, the complete mitochondrial genome of N. elegans was sequenced. It was determined to be 17, 460 bases, and included 13 protein-coding genes (PCGs), 22 tRNA genes, 2 ribosomal RNA genes and one non-coding region, which is similar to other mammalian mitochondrial genomes. Bayesian inference and maximum likelihood methods were used to construct phylogenetic trees based on 12 heavy-strand concatenated PCGs. Phylogenetic analyses further confirmed that Crocidurinae diverged prior to Soricinae, and Sorex unguiculatus differentiated earlier than N. elegans.